Evaluation of Some Physical, Chemical and Sensory Properties of Kasar Cheese and Its Processed and Analogue Types - Onur Güneşer; Yonca Karagül Yüceer; Musa Yalman (Journal of Agricultural Sciences)
The objective of this study was to evaluate the changes in physical, chemical and sensory properties of the kasar cheese and its processed and analogue types during 90-day storage. Aroma-active compounds in the cheeses were identified by gas chromatography-olfactometry. Sensory properties of the cheeses were determined by descriptive sensory analysis. Differences in basic composition of the cheeses were found. There were also significant differences among the cheeses in terms of meltability, oil separation index, L* and a* values. Whey, cooked, creamy and fermented were the most intense sensory descriptors in the cheeses analyzed on days 1 and 30. However, waxy and animal intensities were much higher in analogue cheese than others. 18 aroma-active compounds were determined in the cheeses during 90 day storage. Diacetyl, acetic acid, butyric acid, 2-/3-methyl butyric acid, 2-acetyl-2-thiazoline, b-ionene, 2-phenylethyl alcohol, maltol, p-cresol, sotolon, d-decalactone and g-dodecalactone were some of the characteristic aroma-active compounds. Kasar cheese was the most liked cheese while analogue cheese was the least liked cheese by consumers